Dielectric properties of strontium titanate and calcium titanate prepared via solid state and mechanical alloying methods - Wong, Yick Jeng (2013)
In this thesis, the phase formation, microstructure, and dielectric properties of strontium titanate (SrTiO3) and calcium titanate (CaTiO3) were investigated. Both samples were prepared using two different techniques, one by solid state reaction technique with the sintering temperature from 1200 to 1400°C at 40°C interval, and another by mechanical alloying method with the sintering temperature from 1000 to 1200°C at 40°C interval. From x-ray diffraction (XRD) analysis at room temperature, a single phase cubic SrTiO3 structure with space group Pm-3m and a single phase orthorhombic CaTiO3 structure with space group Pnma were obtained at 1200°C and above as both samples were prepared by solid state method. For the SrTiO3 samples prepared by mechanical alloying method, the formation of a single phase cubic SrTiO3 structure with space group Pm-3m could be achieved at 1160°C and above; whilst, a single phase orthorhombic CaTiO3 with space group Pnma could be formed starting from 1120°C and above. In all the synthesized samples, the morphological analysis revealed that the grains were in submicron range with the calculated average grain sizes increased with sintering temperature. The real part of relative permittivity εr’, imaginary part of relative permittivity εr”, and loss tangent tan δ have been measured on the sintered samples with respect to frequency range 0.01 Hz-1 MHz and varying temperatures from 25 to 250°C at 25°C interval. Meanwhile, the microwave dielectric measurements in the frequency range 1 MHz-1.5 GHz were also performed at room temperature. In the dielectric analysis at low frequency, εr’ decreased with increasing frequency for both samples prepared by solid state and mechanical alloying methods. The values of εr’ and tan δ showed an increase with the rise in temperature. The loss of all the samples under study at different measured temperatures were characterized by the loss peaks at particular frequencies. It indicated the presence of conductivity relaxation in the material. In the microwave frequency range, εr’ remained constant for the SrTiO3 and CaTiO3 prepared by both methods, notably in the frequency range 107-108 Hz, whereas the values of εr” were relatively small which lied in the order of 10-2 in the same frequency range. At 1200°C, the room temperature values of εr’ at 1 and 10 MHz of solid state prepared SrTiO3 sample were about 27.7 and 43.6 respectively, while the room temperature values of εr’ of mechanical alloyed SrTiO3 samples were about 58.8 and 65.7 respectively. The room temperature values of εr’ at 1 and 10 MHz for the solid state prepared CaTiO3 samples sintered at 1200°C were about 19.4 and 42.4 respectively, while were about 132 and 205 respectively for the mechanical alloyed CaTiO3 samples. For all the investigated samples, εr’ values increased with increasing sintering temperature in the low and microwave frequency range due to the grain growth with respect to increasing sintering temperature. The grain growth rate of mechanical alloyed samples was larger than that of solid state prepared samples. Hence, the values of εr’ were found to be enhanced in the samples prepared by mechanical alloying method. It was thus concluded that mechanical alloying processing route was thus a good alternative and yielded materials with improved dielectric properties if compared to that solid state method.